SIKSA BATIN DALAM CINTA SEGITIGA: ANALISIS PSIKOLOGI SASTRA NOVEL CINTA DI ANTARA DUA PRIA - Maulana S, Faridh (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The purpose of this research is a novel written together by three authors, namely Putra Gara, Reni Erina and Mayoko Aiko with the title Cinta di Antara Dua Pria. This was chosen because all the characters in the novel has a very prominent psychological dilemma. There is the purpose of this study, the first to find out and describe the elements of plot and character in analyzing this novel, the second is to find out and describe the psychological aspects of the character. The theory used in this research is the theory of the structure of personality. The findings of this research show that people who have a strong personality to be able to deal with problems in life. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: schizophrenia, transformation, defensive.